Ski skating technique and physiological responses across slopesand speeds - Kvamme, B.; Jakobsen, V.; Hetland, S.; Smith, G. (European Journal of Applied Physiology, 2005)
Appropriate technique choice may affect ski performance. V2 ski skating technique has in recent years become more widely applied on uphill terrain where V1 technique has typically been used. This investigation compared physiological responses of skiers using V1 and V2 techniques during uphill treadmill roller-skiing. Part 1: six skiers from B-level national ski teams participated in technique comparisons performed under six uphill conditions (3, 4, 5, 6, 7, and 8° ) with speeds selected so external work was approximately constant for each slope. The 12 trials of 5-min steadystate skating were randomly distributed across two test sessions of six trials each. Heart rate (HR), oxygen consumption (VO2), blood lactate concentration (La) and rating of perceived exertion (RPE) were measured. Part 2: 15 skiers from A-level and B-level national ski teams participated in V1-V2 technique comparison on constant slope (5°) with five speeds ranging from 2.25 to 3.25 m s-1 . In two test sessions of V1 or V2 skating (randomly assigned for 2 days) similar characteristics as Part 1 were measured. Across all variables consistent responses were observed for both the experimental parts. As slope increased, V2 skating became increasingly costly compared to V1 skating. At constant slope across the range of speeds, V2 was more costly than V1 skating. This suggests that it may be disadvantageous for skiers to use V2 instead of V1 skating technique on moderate to steep uphill terrain. Doing so may result in elevated HR, La, and VO2 compared to V1 skating at the same speed.